Vulnerability to risky sexual behavior among patients with severe mental illness in Uganda - C. Birungi; J. Ssebunnya; N. Kiwanuka; N. Nakasujja; E. Kinyanda (Springer, 2024)
Abstract Background The relationship between severe mental illness and risky sexual behaviors, defined as acts associated with a higher risk level is notably significant in sub-Saharan Africa. In Uganda, mental disorders have been substantially correlated with unsafe sexual practices, contributing to the global burden of risky sexual behaviors. The consequential outcomes, such as sexually transmitted diseases, has resulted into a significant challenge in managing severe mental illness and potentially increased risky sexual behaviour. There is an urgent need to identify and understand factors specific to Uganda that amplify the vulnerability of severe mental illness patients to risky sexual behaviors. This study aimed to understand the vulnerability factors to risky sexual behaviour in severe mental illness in central and south-western Uganda, seeking to inform the development of tailored and effective intervention strategies to address this critical issue. Methods This was a qualitative descriptive study that was carried out at Butabika and Masaka hospitals in Uganda, involving a varied group of 32 individuals, comprising 12 persons with diagnosed Severe Mental Illness (Schizophrenia, Bipolar Affective Disorder, or Recurrent Major Depressive Disorder) and to risky sexual behaviors, 8 caregivers (who had patients with severe mental illness and to risky sexual behaviors) and 12 mental health specialists, (who had treated these participants). Purposive sampling was done by intentionally selecting participants based on specific attributes relevant to the research question and the objective of the study which was to explore the factors contributing vulnerability to risky sexual behaviour in severe mental illness in central and south-western Uganda. The interviews were conducted, centered on personal experiences and influences on risky sexual behaviors for the persons with severe mental illness, targeting insights into the nuanced interplay of severe mental illness and sexual behavior. For caregivers and mental health specialists, the interviews were conducted to gain a comprehensive understanding of the unique challenges, perspectives, and experiences they encounter in providing support and treatment respectively. The interviews were tape-recorded and transcribed verbatim. Framework analysis of transcribed interviews, using NVivo11 software that helped to systematically organize and code data within the predetermined and emergent thematic framework, we were able to identify patterns and themes to address the research question and objective. Results The study findings underscored a pervasive pattern of engaging in risky sexual behavior among individuals coping with severe mental illness, a growing concern traditionally associated with sexually transmitted infections like HIV and AIDS, unwanted pregnancies, and sexual encounters with strangers. This problem was largely attributed to factors such as compromised judgment due to underlying morbidity, abnormally high libido, poverty, desperation, and inadequate social support. Additionally, sexual deprivation, often a result of stigma, discrimination, and prolonged periods of hospitalization, was found to contribute to irresponsible and risky sexual acts. Respondents also highlighted certain practices and structural weaknesses within hospital environments, such as stripping patients naked when going to seclusion rooms and inadequate patient monitoring. Conclusions The findings underscore the need for targeted interventions addressing both individual and structural factors to alleviate the risks associated with sexual behavior among individuals with severe mental illness.